2017
DOI: 10.1016/j.addbeh.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana and other substance use among male and female underage drinkers who drive after drinking and ride with those who drive after drinking

Abstract: The study sought to describe the occurrence of adolescent driving after drinking (DD) and riding with a driver who had been drinking (RWDD) and associations with substance use for both males and females. As part of screening for a randomized controlled trial, we surveyed 16-20year olds (N=3418) recruited from an emergency department (ED) and analyzed data from those reporting past-year alcohol consumption (n=2150, 58% females). DD was reported by 22% of females and 28% of males and RWDD was reported by 39% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
(22 reference statements)
0
7
0
1
Order By: Relevance
“…However, the rate of driving after alcohol use was lower than has been reported in other studies of AYAs without type 1 diabetes. It is estimated that nearly one-fourth of AYAs in the general population drive after consuming alcohol, whereas only about 10% of AYAs with type 1 diabetes in our study reported doing so (23). This finding suggests there is likely some effective education and awareness around the impact of alcohol on blood glucose, specifically that alcohol contributes to acute and delayed-onset hypoglycemia and can also exacerbate the effects of hypoglycemia (33,34).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, the rate of driving after alcohol use was lower than has been reported in other studies of AYAs without type 1 diabetes. It is estimated that nearly one-fourth of AYAs in the general population drive after consuming alcohol, whereas only about 10% of AYAs with type 1 diabetes in our study reported doing so (23). This finding suggests there is likely some effective education and awareness around the impact of alcohol on blood glucose, specifically that alcohol contributes to acute and delayed-onset hypoglycemia and can also exacerbate the effects of hypoglycemia (33,34).…”
Section: Discussionmentioning
confidence: 52%
“…Driving after alcohol or marijuana use increases the risk of motor vehicle accidents (MVAs), and prevalence of driving after use of these substances has been reported to be high among AYAs (21). Studies have indicated that, in the United States, 12-28% of AYAs report driving under the influence of alcohol, and 3-11% report driving under the influence of marijuana (18,22,23). Additionally, use of cell phones and texting are major causes of distracted driving and MVAs (24).…”
mentioning
confidence: 99%
“…The findings of the present study document that specific adolescent health risk behaviors are associated significantly with adolescents' own and their perceptions of peers' underage alcohol use as indexed by a brief, developmentally informed 2-item underage alcohol use screening tool. Previous studies have highlighted the role of adolescents' risky patterns of alcohol use in the increased likelihood of DUI or riding with an intoxicated driver (Buckley et al, 2017) as well as other forms of substance use, with increases in both short-and long-term risk for morbidity and mortality (Moss, Chen, & Yi, 2014;Terry-McElrath, O'Malley, & Johnston, 2013). Underage alcohol consumption in the company of peers is also significantly associated with a wide range of sexual and other risk behaviors during adolescence (Hingson & White, 2014;Monahan, Rhew, Hawkins, & Brown, 2014;Stueve & O'Donnell, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another study of over 2000 young adults found that 15.2% reported any type of DUI, with the greatest proportion (5.02%) reporting driving after marijuana use and 4.34% after using alcohol and 2.41% after using marijuana and alcohol (Li, Simons-Morton, Gee, & Hingson, 2016). In addition, recent research has indicated that marijuana use is also a predictor of DUI of alcohol, and riding with someone DUI of alcohol (Buckley et al, 2017). …”
Section: Discussionmentioning
confidence: 99%